POLITIK HUKUM ISLAM DI INDONESIA (KAJIAN REFORMASI HUKUM DALAM KERANGKA PEMIKIRAN IBNU TAIMIYAH) - Rosman, Edi (Alhurriyah, 2017)
Islam and Indonesia are two unseparated parts. The born and the existence of Republic of Indonesia was a big result of the community of the nation and Islam has taken the biggest part of it. Islamic political views and Islamic community with all of their problems are the historical richness that could not be forgetten. Nowadays, this Nation still needs the participation of Islamic political views and actors as majority. However, why they are important? How is the correlation between the actual Islamic political situations in Indonesia with the Islamic political views of Ibn Taimiyah as the most popular Islamic scolars all the time. In Indonesia Islamic have important role in politic because actually, this Nation will be never founded without His bless. As the consequences, all of the Indonesian Moslem people should participate in any aspects such as in politic to build this Country as the expression of thankfulness. Islamic politic act and Islamic law, at present and future, will be an accordance each other if they are formulated in Islamic univesiality frame. The term â€œIslam rahmatan lilâ€™ alaminâ€ (in English means â€˜the boon of the universeâ€™) interpreted as the plurality of Indonesia. Ibn Taimiyah as the Islamic scholars who has born in modern age has political framework that aligned with Indonesia political views. The law reformation may be enforced if this Nation has good and clean government (wilÃ¢yat al-shÃ¢lih). The good and clean government is the trusted government that runs the Nation conforms to the mandate of the people and the constitution of the Nation. Islam dan Indonesia adalah dua hal yang tidak dapat dipisahkan. Lahir, berdirinya dan masih eksisnya Negara Kesatuan Republik Indonesia merupakan hasil perjuangan umat Islam bersama-sama dengan komponen bangsa lainnya. Dalam kontek tersebut, politik Islam dan Umat Islam dengan berbagai dinamikanya menjadi kekayaan historis yang tidak boleh dilupakan. Saat inipun, Negara Kesatuan Repoblik Indonesia sangat membutuhkan partisipasi politik Umat Islam yang secara kuantitatif masih mayoritas. Mengapa pentingnya peran politik umat Islam? Dan bagaimana politik hukum Islam saat ini dan dimasa yang datang jika dilihat dari kerangka berpikirnya Ibnu Taimiyah?. Pentingnya politik umat Islam ialah karena Negara ini lahir atas berkat Rahmat Allah SWT. Sebagai konsekuensinya, Umat Islam wajib bersyukur dengan berpartisipasi aktif dalam berbagai bidang dan tidak terkecuali dalam bidang politik. Politik Islam dan Hukum Islam sekarang dan dimasa yang akan datang akan senafas dengan keindonesiaan jika diformulasikan dalam bingkai universalitas Islam itu sendiri. Islam rahmatan lil â€˜alamin diterjemahkan dalam pluralitas keindonesiaan. Ibnu Taimiyah sebagai seorang Ulama yang lahir di Abad Modern ini, memiliki kerangka berpikir politik yang selaras dan cocok dengan dinamika, kontekstual dan fundamental politik hukum Islam di Indonesia. Reformasi Hukum (istiâ€™malul Ishlah) akan dapat dilaksanakan jika Negara ini memiliki pemerintah yang baik (wilayatus shalih). Pemerintah yang baik adalah pemerintah yang melaksanakan amanah kenegaraan sesuai dengan amanat yang diberikan oleh rakyat dan Undang-undang Dasar.